2021
DOI: 10.23887/jpbi.v9i1.33811
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Grammar and Structure Problems Faced by Indonesian TOEFL Participants

Abstract: The TOEFL test is one of the requirements to pass the Thesis exam at several universities in Indonesia. Grammar and Structure Score is the lowest score, and it becomes a problem for the test takers. This study aimed to analyze the factors of Grammar Structure difficulties experienced by students in solving TOEFL questions. This research approach is descriptive qualitative with a sample of 20 students and taken by purposive sampling of 70 students. Interviews and questionnaires were conducted as a data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Teachers and learners are exposed to various task-based process to encourage a better participation among learners throughout the lesson (Mathematics, 2016). Grammar problems are indeed one of the most complex problems in learning English, this has also been proven in research on grammar problems in TOEFL test results (Hampp et al, 2021).…”
Section: Introductionmentioning
confidence: 68%
“…Teachers and learners are exposed to various task-based process to encourage a better participation among learners throughout the lesson (Mathematics, 2016). Grammar problems are indeed one of the most complex problems in learning English, this has also been proven in research on grammar problems in TOEFL test results (Hampp et al, 2021).…”
Section: Introductionmentioning
confidence: 68%
“…Reader-response theory within the context of LBT emphasizes the significance of personal interpretation, encouraging students to articulate and defend their viewpoints, fostering a sense of autonomy and intellectual agency. Literature-Based Teaching emerges as a theoretical concept that envisions literature not merely as a supplementary tool but as the epicenter of a transformative educational experience (Vandrick, 2018); (Lumentut & Lengkoan, 2021); (Hampp et al, 2021). This pedagogical framework posits that through the judicious incorporation of literature, educators can cultivate a fertile ground for intellectual, emotional, and interdisciplinary growth, thereby nurturing well-rounded individuals poised for active engagement with the complexities of the world.…”
Section: Literature-based Teachingmentioning
confidence: 99%
“…In addition, [2] found that for most Indonesians, the goal of learning English as a foreign language is to be able to communicate in English. When learning English, learners first need to know about four language skills and then what comes with those skills, Speaking, reading, writing, and Listening [3]. The components of these skills are pronunciation, grammar or structure, vocabulary, and spelling.…”
Section: Introductionmentioning
confidence: 99%